The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/ijms24043933
|View full text |Cite
|
Sign up to set email alerts
|

HSPs/STAT3 Interplay Sustains DDR and Promotes Cytokine Release by Primary Effusion Lymphoma Cells

Abstract: Primary effusion lymphoma (PEL) is a rare and aggressive B-cell lymphoma, against which current therapies usually fail. In the present study, we show that targeting HSPs, such as HSP27, HSP70 and HSP90, could be an efficient strategy to reduce PEL cell survival, as it induces strong DNA damage, which correlated with an impairment of DDR. Moreover, as HSP27, HSP70 and HSP90 cross talk with STAT3, their inhibition results in STAT3 de-phosphorylation and. On the other hand, the inhibition of STAT3 may downregulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…Even if the STAT3 dephosphorylation was slightly further reduced by AZA/AG490 combination compared to AG490, a stronger downregulation of c-Myc, Cyclin D1 and HSP27 was observed ( Figure 2 C). The overexpression of these molecules has been closely correlated with the survival and progression of cancers, including PEL [ 29 , 30 ]. Together, these results suggest that 5-AZA could be a promising strategy to increase the sensitivity of PEL cells to treatment with STAT3 tyrosine inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…Even if the STAT3 dephosphorylation was slightly further reduced by AZA/AG490 combination compared to AG490, a stronger downregulation of c-Myc, Cyclin D1 and HSP27 was observed ( Figure 2 C). The overexpression of these molecules has been closely correlated with the survival and progression of cancers, including PEL [ 29 , 30 ]. Together, these results suggest that 5-AZA could be a promising strategy to increase the sensitivity of PEL cells to treatment with STAT3 tyrosine inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…The collaboration between HSPs and STAT3 has been documented in various biological processes. A positive feedback loop involving HSPs and STAT3 assumes a pivotal role in sustaining DNA Damage Response (DDR) and preventing DNA damage in Primary Effusion Lymphoma (PEL) cells [69]. The Stat3 inhibitor, Stattic, impedes the acquisition of thermotolerance by suppressing mild heat shockinduced Stat3 phosphorylation and Hsp105 expression [70], thereby implicating the regulatory influence of STAT3 on Hsp105.…”
Section: Discussionmentioning
confidence: 99%
“…Several HSPs play a role in the stability of the molecules involved in DNA repair [8,9]. Here, we explored the impact of HSP110 inhibition on DNA damage and observed that γH2AX-positive foci increased in BC3 and BCBL-1 silenced cells (Figure 3A), suggesting that the reduction in this HSP induced DNA damage.…”
Section: Hsp110 Knockdown Induces Dna Damage By Impairing Hr and Nhej...mentioning
confidence: 95%
“…We have recently reported that several HSPs, including HSP27, HSP70, and HSP90, overlap in their capacity to sustain the stability of several DDR molecules in PEL cells, contributing, also for that reason, to the survival of this aggressive B cell lymphoma. Moreover, in the above-mentioned study, we reported that the inhibition of these three HSPs inhibited STAT3 phosphorylation and reduced pro-inflammatory cytokine release, which may not only affect the survival of cancer cells but also contribute to shaping the tumor microenvironment [9]. Among the HSPs, one of the less studied is HSP110, a holdase chaperone, considered a non-canonical HSP70 protein.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation